Maternità surrogata e identità frammentate: quale legame conta davvero? (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Following the increasingly jurisprudential pronouncements aimed at recognizing a legal tie between the intended parent and the child born as a result of surrogacy, the article questions the right to know own biological origins and the relation with the surrogate mother from which the gestation for others it deliberately detaches it from birth, helping to create fragmented identities in the name of the alleged best interest of the child.
Keywords: Right to know genetic origins; surrogacy; personal identity; best interest of the child; assisted reproduction